PWE-144 7-year experience of two stage minimally invasive oesophagectomy with intrathoracic anastomosis (mio-2) in a single uk centre. (22nd June 2015) - Noble, F; Underwood, T; Sharland, D; Byrne, J; Kelly, J
Abstract : Introduction: The 2014 report of the National OesopahgoGastric Cancer Audit (NOGCA) identified an increasing number of patients who were treated with minimally invasive (MIO) or hybrid operations (41.5%). Overall complications were similar to open surgery, but a significant increase in anastomotic leak (AL) after MIO was identified (11.7% vs. 6.7%). Totally minimally invasive oesophagectomy with intrathoracic anastomosis (MIO-2) has been performed at University Hospital Southampton NHS Foundation Trust since 2008 and we present a review of this consecutive series. Method: A prospectively collected database of clinic-pathological and operative variables from consecutive patients undergoing oesophagogastric resection between January 1, 2005 and February 27, 2015 was reviewed. Statistical analysis was performed in SPSS. Results: 147 patients (78% male, 22% female) underwent MIO-2, beginning in June 2008. Patient demographics were: median age 67 years (33–85), median BMI 26 (16–37), ASA 1 6.8%, ASA 2 64.6%, ASA 3 27.9%, ASA 4 0.7%. One patient had surgery for achalasia and 3 for HGD/Tis; the remainder had invasive cancer. 65% of patients had T3 disease on preoperative staging, with 65.3% having evidence of lymph node involvement (N1+). Median operative duration was 319 min (180–530 min) and median blood loss of 205 ml (0–5000 ml). In 11 (7.5%) cases the thoracic component was converted to open. There were 3 in-patient deaths (2.0%) including one intraoperative mortality. Major complications (Clavien-Dindo 3–4) were observed in 19% of cases with 11 anastomotic leaks (7.5%) and a reoperation rate of 9.6%. An R0 resection was achieved in 81.9% of cases with a median lymph node yield of 21 (2–62). Median length of hospital stay was 11 (6–96) days. Conclusion: MIO-2 can be performed in the UK with acceptable perioperative morbidity, mortality, and oncological efficiency. Disclosure of interest: F. Noble: None Declared, T. Underwood Grant/Research Support from: MRC, D. Sharland: None Declared, J. Byrne: None Declared, J. Kelly: None Declared.